Epidemiologia das infecções hospitalares em centro de terapia intensiva de adulto - Patricia Martins (2006)
The present study is a historical cohort with data collected in AdultIntensive Therapy Care Units, describing several epidemiological characteristics of nosocomial infections. The study was conducted with adult patients and 19,533 of them were studied. The mean average for nosocomial infection incidence was 18.72% and 36,22 / 1,000 patient days. Pneumonias were the site most frequently determined and caused 6.01% of nosocomial infections, being 84.07% of them related to mechanical ventilation. Laboratory and clinical sepsis reached 3.6% ofadmissions and sepsis related to central venous catheter occurred in 29.73% of the cases, being the majority (98.08%) 205 cases related to punctured catheters. There were 826 cases of urinary tract infection, being 650 cases related to urinary catheter, reaching a total of 78.69% of the cases. Urinary tract infection incidence related to urinary catheter oscillated from 3.55 to 21.26 per 1.000/ urinarycatheter- days, with average of 14.08 per 1.000 urinary- catheter- days. The most frequent sites were pneumonia in 1,174 patients (6.01%), urinary tract infection in826 patients (4.23%), laboratory and clinical sepsis in 703 cases, representing 3.60% of the admissions and 333 cases of circulatory system infection. The highest rate of invasibility, which was 0.64 was related to use of the central venous catheter. The rate of invasibility to use of the mechanical ventilation was 048 and to use of urinary catheter was 0,46.